The effects of welfare time limits on access to financial resources: Evidence from the 2010s - Gabrielle Pepin (W.E. Upjohn Institute for Employment Research, 2020)
The Personal Responsibility and Work Opportunity Reconciliation Act of 1996 established the Temporary Assistance for Needy Families (TANF) program within the United States. TANF mandated 60-month lifetime time limits for federal cash assistance dollars. Because states reserve the right to set their own stricter or more generous time limits, the 60-month lifetime limit did not bind in all cases. In recent years, however, several states imposed TANF time limits for the first time or made existing time limits more stringent. Using administrative and survey data, I find that stricter time limits decrease annual TANF participation by 22 percent and annual transfer income by 6 percent. Consistent with binding TANF work requirements, widespread unemployment, and increases in employment among those on the welfare caseload, stricter time limits do not tend to increase employment or earnings among single mothers in states without generous TANF programs at baseline. Evidence suggests that macroeconomic conditions and the labor market potential of TANF recipients play large roles in determining labor-supply effects of decreased TANF generosity.
Keywords: H53; I38; J22; 330; Temporary Assistance for Needy Families; time limits; synthetic control method; difference-indifferences; participation